Antioxidant activity of phenylethanoid glycosides on glutamate-induced neurotoxicity. Issue 11 (2nd November 2019) - Ji, Shi-Liang; Cao, Ke-Ke; Zhao, Xing-Xing; Kang, Nai-Xin; Zhang, Ying; Xu, Qiong-Ming; Yang, Shi-Lin; Liu, Yan-Li; Wang, Cheng
ABSTRACT: Exposure of PC12 cells to 10 mM glutamate caused significant viability loss, cell apoptosis, decreased activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) as well as increased levels of malondialdehyde (MDA). In parallel, glutamate significantly increased the intracellular levels of ROS and intracellular calcium. However, pretreatment of the cells with acteoside and isoacteoside significantly suppressed glutamate-induced cellular events. Moreover, acteoside and isoacteoside reduced the glutamate-induced increase of caspase-3 activity and also ameliorated the glutamate-induced Bcl-2/Bax ratio reduction in PC12 cells. Furthermore, acteoside and isoacteoside significantly inhibited glutamate-induced DNA damage. In the mouse model, acteoside significantly attenuated cognitive deficits in the Y maze test and attenuated neuronal damage of the hippocampal CA1 regions induced by glutamate. These data indicated that acteoside and isoacteoside play neuroprotective effects through anti-oxidative stress, anti-apoptosis, and maintenance of steady intracellular calcium. Graphic Abstract: : Protective effect of acteoside and isoacteoside on glutamate-induced cytotoxicity in PC12 cells.